Bi-dimensional values and attitudes toward online fast food-buying intention during the COVID-19 pandemic: An application of VAB model - Yan, Chen; Siddik, Abu Bakkar; Masukujjaman, Mohammad; Dong, Qianli; Hamayun, Muhammad; Guang-Wen, Zheng; Ibrahim, Abdullah Mohammed (Frontiers in Nutrition, 2022)
The purpose of the study is to determine the factors of online fast food-buying intention among Bangladeshi Millennials during the COVID-19 pandemic. The study adopted the Value-Attitude-Behavior (VAB) model and designed as higher-order constructs model to predict buying intention. Using a quantitative method (i.e., cross-sectional survey), data were collected from 325 respondents via a structured questionnaire and subsequently analyzed using Structural Equation Modeling (SEM) through AMOS software. The study outcomes revealed that convenience and food quality generate utilitarian values, while subjective norms and novelty-seeking form hedonic values. Also, the utilitarian and hedonic values significantly affect the cognitive and affective attitude. As opposed to food quality, the cognitive attitude, affective attitude, self-identity and subjective norms were observed to affect behavioral intention, with affective attitude producing the strongest influence, albeit high explanatory power of the model. Consequently, this study offers a number of theoretical and policy implications to design better interventions that address public health about fast food consumption.